Development of a project tracking system for the Commission on Higher Education (CHED) funded projects - Tercia, Adelma C.; Talisayon, Serafin (University of the Philippines Diliman, Quezon City Technology Management Center, 2017)
The Commission on Higher Education (CHED) has been funding Research and Development and Extension (RDE) projects of Higher Education Institutions (HEIs) through the Research and Management Division (RMD). As a government agency, proper management of funds is imperative. Hence, the RMD is tasked to not only appropriate RDE funds to qualified recipients but also to ensure that project deliverables are completed as promised.
Given these responsibilities of the RMD in grant management, a need to strengthen the monitoring and evaluation (M&E) was brought to the table.
Using proper KM tool and practices found in relevant literature, a project called Project Tracking System (PTS) was established. The PTS enabled the RMD Team to view and monitor the progress of ongoing projects real-time. It also benefited the project implementer in preparation and submission of their progress reports on time.
With the success of the project, it is further recommended to formulate explicit M&E policy. The conduct of users training and integrating the use of the PTS in the M&E policy will further strengthen the M&E process of the RMD. Moreover, cascading the learning and the system to other offices that fund and manage projects is proposed as the way forward.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Commission on Higher Education (CHED).; Web databases -- Design; Project management -- Computer programs; Project Tracking System